The effect of different soil pH level on the availability and the uptake of macro plant nutrient by oil palm (Elaeis guineensis) seedling / Syahidil A. Salam - A. Salam, Syahidil (Faculty of Plantation and Agrotechnology, 2015)
The effects of different levels of soil pH on the availability and uptake of plant macronutrient by oil palm seedling (Elaies guineensis) was observed by planting them in the polybag that was filled with the soil of different pH. The soil pH played an important role in determining the availability of macronutrients. In this experiment, the soil's pH were adjusted from high acidity to high alkalinity. The soil's pH were adjusted by using sulphuric acid(H₂S0₄) and sodium hydroxide(NaOH) and applied to certain amount onto the soil. The availability of soil nutrients were marked by the content of the nutrient in the soil. The nutrient left in the soil was probably due to the unavailability of the nutrients to be uptake by oil palm seedlings roots. At the end of finding, it was found that the different soil pH has no significant effect to oil palm seedlings growth response which is due to the oil palm tolerance to change in soil ph.